Analisis Algoritma C4.5 dalam Mengukur Tingkat Kepuasan Staf terhadap Kinerja Teknisi Komputer - Aliyah, Siti; Desi, Efani; Nasution , Fitri Pranita; Tahel, Fithry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study was conducted to determine the level of computer technician performance on staff satisfaction so that staff do not face obstacles in working so that the teaching and learning process and human resource process run effectively. By knowing the level of staff satisfaction, the academic party can easily find out the level of computer technician performance, so that if there are inappropriate results, the academic party can quickly fix and improve the performance of computer technicians. This study was conducted in measuring staff satisfaction with the performance of computer technicians at Universitas Potensi Utama. The method used by the author in this study is the C4.5 algorithm method by producing rules, accuracy values and decision trees, for the data collection process which will be carried out using a questionnaire distributed to staff via a google form link that can be assessed. The data used by the author is staff data totaling 129 respondents. The measurement results obtained using the C4.5 algorithm method are an accuracy level of 106 data with a total of 82% with the root attribute Reliability, with branch attributes namely Empathy and Tangibles. It is hoped that the results of this study can continue to be carried out periodically to improve the performance of computer technicians according to their competence so that the existing system can continue to run very well.